Applying theoretical models of positive emotion to improve pediatric asthma: A positive psychology approach. Issue 10 (11th August 2021) - Jenkins, Brooke N.; Moskowitz, Judith; Halterman, Jill S.; Kain, Zeev N.
Abstract: Positive emotion, encompassing feelings such as joy and happiness, has been shown to predict a multitude of health outcomes. However, the role of positive emotion in pediatric asthma is not understood. No work to date has examined how positive emotion may offer benefits to children and adolescents with asthma. Based on theory and models of positive emotion and health, we hypothesize that positive emotion may improve asthma outcomes through mediators such as health behaviors and health‐relevant physiological functioning. Moreover, boosting positive emotion during times of stress may be particularly relevant in mitigating asthma symptoms. In the present commentary, we elaborate on the hypothesized mechanisms behind such associations grounded within positive emotion theoretical frameworks. Additionally, we summarize the methodologically rigorous work of positive emotion interventions in other clinical settings to propose that positive emotion could be a useful tool in the management of pediatric asthma.